Hubungan Antara Pola Makan dan Aktivitas Fisik Dengan Kejadian Anemia pada Ibu Hamil di Wilayah Kerja UPTD Puskesmas Non Rawat Inap Indraloka Jaya Kecamatan Way Kenanga Kabupaten Tulang Bawang Barat - Ningsih, Dwi Rahayu; Nurhartanto, Adhi; Kustiani, Ai (CV. Rayyan Dwi Bharata, 2024)
Anemia is a medical condition that typically arises when there is a significant decrease in the number of red blood cells in the body. During pregnancy, anemia generally occurs in the first and third trimesters with hemoglobin (Hb) levels below 11 g%, and in the second trimester with Hb levels below 10.5 g%. This study aims to examine the relationship between dietary patterns and physical activity with the incidence of anemia among pregnant women in the working area of Puskesmas NoN Rawat Inap Indraloka Jaya, Way Kenanga District, Tulang Bawang Barat Regency. This descriptive correlational study employs a cross-sectional design conducted from July 10 to 16, 2024. The sampling method used is total population sampling, with the sample size equal to the total population of 68 individuals. The statistical test applied is the Chi-Square test. Data collection was performed through interviews and Hb checks using a GcHB digital device. The results show that the majority of pregnant women with inadequate dietary patterns have anemia (23.5%), while those with light physical activity and anemia account for (25.0%). Statistical test findings indicate a significant correlation between dietary patterns and the incidence of anemia with a P-value of 0.000, and a significant relationship between physical activity and the occurrence of anemia with a P-value of 0.000. This suggests that the relationship between dietary patterns, physical activity, and the incidence of anemia is very strong.